Stress Level and Use of Coping Strategies Among Nursing Students During the Pandemic Period: Looking Back and Reflecting its Impact - John Mark Asio; Carole Garcia (Journal of Healthcare and Biomedical Science, 2023)
This study aims to assess the stress level of nursing students in different settings and their use of coping strategies during the pandemic. The researchers used a descriptive-correlation research design for 288 nursing students purposively selected for the study. The study took place during the academic year of 2022-2023. The study also employed three (3) research tools for the data gathering. It subjected the data to descriptive and inferential analysis using SPSS 23. In general, the study found that in terms of stress level, the nursing students remarked “moderately high,” as for the coping strategies, they “sometimes” used them. The inferential computation also observed significant variations in the stress level in the study in terms of gender, age, school, and year level. Moreover, there was a low positive relationship between the level of stress and the use of coping strategies among the nursing students. To confirm the connection, perceived stress and external stressors were significant predictors of the use of coping strategies among nursing students. The researchers then gave several implications at the end of the study.